Three essays in macro-finance - Valente, João Paulo (2019)
This dissertation consists of three essays in Macro-Finance. The first two papers study tail risk in the hedge fund industry, and the last paper investigates the effects of fiscal irresponsibility in a monetary union under the Fiscal Theory of Price Level (FTPL) framework. In the first paper, we rely on the convergence trading model and the increasing participation of high-frequency trading (HFT) in the US fund industry to propose a new tail risk measure, HFTR. The growth of HFT raised the number of hedge funds that follow similar strategies and market signals, increasing trade overcrowding. Together with funds’ leverage, overcrowding may cause a high initial loss trigger fire sales that could affect the entire financial industry through a loop of investment positions liquidation. Kondor’s (2009) convergence trading equilibrium model illustrates well this mechanism. Motivated by the importance of these effects inside the fund industry, we estimate tail risk using the cross-section of hedge fund returns. We show that US hedge funds are exposed to our tail risk and that it helps to explain the cross-sectional dispersion of funds returns. We also compare our index with other tail risk measures in the literature and find that ours seems to better capture both the hedge funds’ exposure to extreme risks and the cross-sectional dynamic of returns. In the second essay, we estimate tail risk using different estimation methods for the Brazilian hedge fund industry. The Brazilian hedge fund data is unique because it contains daily returns of all Brazilian funds, allowing us to compute tail risk measures that rely on daily observations and avoiding well-known biases to hedge fund datasets. Differently from the US, every investment fund in Brazil must report returns (and other relevant information) to the regulatory agency (CVM) daily. The database we use contains the universe of investment funds in Brazil, dead or alive, avoiding selection, survivorship, and instant history biases. We compared six different methodologies across three different estimation approaches and two different returns data (equity and hedge funds). We find that tail risk estimates are very different, not only across asset classes but also across methodologies. We also show that, although hedge funds in Brazil seem to exhibit more exposure to equity tail risk, hedge fund tail risk entails a higher predictive ability to performance both over time and cross-sectionally In the last paper, we show that if the fiscal policy of a fiscally irresponsible member of a monetary union follows a Markov Switching process with two regimes (responsible and irresponsible), the central bank may be able to determine the price level through an active monetary policy. This result contradicts the findings of Woodford (1996) and Bergin (2000). In our case, the only requirement is to the irresponsible regime be short-lived, or an aggressive primary surplus response to debt grow in the responsible (Ricardian) regime. We also show that once the economy has a unique equilibrium, the impact of the unstable fiscal rule is negligible.